The Implementation of Literary Works for Promoting Student Involvement in Learning English Grammar - Asfi Aniuranti; Dinar Faiza; Yasinta Wulandari (Prodi PBA Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2021)
Nowadays, every teaching and learning process is supposed to apply a student-centered concept in which the pupils are the center of the process, and they are encouraged to participate actively in the process. Therefore, all education levels have implemented this concept, including the university level. Unfortunately, many pupils are still passive during the teaching process. This phenomenon also appears in the English Language Teaching Department of Universitas Nahdlatul Ulama Purwokerto. The low participation of the students happens in all classes, including grammar class. Based on the pre-observation process in a grammar class, the average score of student participation was only 58.82%. From seven categories of student participation, two indicators were still 0% called asking a question and giving constructive or positive comments to the teacher or other students. There was also one category that only achieved 41.18%. Besides, the atmosphere was not conducive since some students talked to their classmates and looked quite bored. Based on this condition, the researchers decided to do action research. After doing a literature study, we agreed to use literary works to overcome the problem. The research was done in one cycle that consisted of three meetings. The instruments used for collecting the data were an observation sheet of student participation and a teacher observation sheet. The data gathered were analyzed using simple statistics like percentage and average score, then the analysis presented through diagram and words. The literary works used in this study were a short story, a film script, and a novel. This action research is successful if the percentage of student involvement can achieve 65%. The result reveals that student participation was getting better after the implementation of literary works in the teaching and learning process. In the first action, the average percentage was 69.29 %, then it became 75.89% in the second meeting. In the third act, the student involvement achieved 78.15%. The most impressive finding appeared in the third meeting. Three students asked questions. Asking questions as one of the indicators of participation did not appear in the first and the second meeting. The atmosphere was getting conducive since the implementation of the literary works in the grammar class. In short, this action research is successful in boosting student involvement in grammar class.